Rapid decrease of soil erosion rates with soil formation and vegetation development in periglacial areas. Issue 12 (23rd July 2020) - Musso, Alessandra; Ketterer, Michael E.; Greinwald, Konrad; Geitner, Clemens; Egli, Markus
Abstract : Soil erodibility of moraine soils decreases exponentially with age, Moraines become geomorphologically stable after 10–14 ka, The lithology did not have an impact on the erodibility. Abstract: High mountainous areas are geomorphologically active environments which are strongly shaped by redistribution of sediments and soils. With the projected climate warming in the twenty‐first century and the continued retreat of glaciers, the area of newly exposed, highly erodible sediments and soils will increase. This presents a need to better understand and quantify erosion processes in young mountainous soils, as an increase in erodibility could threaten human infrastructure (i.e. hydroelectric power, tourist installations and settlements). While soil development is increasingly well understood and quantified, a coupling to soil erosion rates is still missing. The aim of this study was, therefore, to assess how soil erosion rates change with surface age. We investigated two moraine chronosequences in the Swiss Alps: one in the siliceous periglacial area of Steingletscher (Sustenpass), with soils ranging from 30 a to 10 ka, and the other in the calcareous periglacial area of Griessgletscher (Klausenpass) with surfaces ranging from age of 110 a to 13.5 ka. We quantified the erosion rates using the 239+240 Pu fallout radionuclides and compared them to physical and chemical soil properties and the vegetation coverage. We found no significant differences between the two parent materials. At both chronosequences, the erosion rates were highest in the young soils (on average 5−10 t ha ‐1 a ‐1 soil loss). Erosion rates decreased markedly after 3−5 ka of soil development (on average 1−2.5 t ha ‐1 a ‐1 soil loss) to reach a more or less stable situation after 10−14 ka (on average 0.3–2 t ha ‐1 a ‐1 ). Climate change not only causes glacier retreat, but also increased sediment dynamics. Depending on the relief and vegetational development, it takes up to at least 10 ka to reach soil stability. The establishment of a closed vegetation cover with dense root networks seems to be the controlling factor in the reduction of soil erodibility. © 2020 John Wiley & Sons, Ltd.